Laboratory analogue of a supersonic accretion column in a binary star system - J. E. Cross; G. Gregori; J. M. Foster; P. Graham; J. -M. Bonnet-Bidaud; C. Busschaert; N. Charpentier; C. N. Danson; H. W. Doyle; R. P. Drake; J. Fyrth; E. T. Gumbrell; et al. (Nature Communications, 2016)
Stationary radiative shocks are expected to form above the surface of highly-magnetized white dwarves in binary systems, but this cannot be resolved by telescopes. Here, the authors report a laboratory experiment showing the evolution of a reverse shock when both ionization and radiative losses are important.